2016
DOI: 10.1037/tep0000131
|View full text |Cite
|
Sign up to set email alerts
|

Doctoral students’ knowledge of educators’ problems of professional competency.

Abstract: We surveyed doctoral students in APA-accredited programs (clinical psychology PhD, counseling psychology PhD, and clinical psychology PsyD; n ϭ 939) and CACREP-accredited counseling/counselor education programs PhD (n ϭ 345) to investigate their knowledge of educators' problems of professional competency (PPC). Findings suggest the majority of respondents are aware of educators with PPC and are affected by these interactions. Areas such as educators' unprofessional behavior (e.g., dishonesty, excessive tardine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…A final curriculum consideration worth noting is the observation that competency problems among faculty often become apparent to trainees within the context of coursework (e.g., excessive absences, tardiness, poor emotion regulation, inadequate boundaries, dishonesty, and cultural insensitivity) and disrupt student learning (Furr & Brown-Rice, 2016). Although most trainees were aware of faculty with competency problems and had talked with other trainees about those faculty, the majority of trainees did not know how to appropriately address their concerns.…”
Section: Curriculummentioning
confidence: 99%
“…A final curriculum consideration worth noting is the observation that competency problems among faculty often become apparent to trainees within the context of coursework (e.g., excessive absences, tardiness, poor emotion regulation, inadequate boundaries, dishonesty, and cultural insensitivity) and disrupt student learning (Furr & Brown-Rice, 2016). Although most trainees were aware of faculty with competency problems and had talked with other trainees about those faculty, the majority of trainees did not know how to appropriately address their concerns.…”
Section: Curriculummentioning
confidence: 99%
“…Furthermore, the long-term benefits of being graduate mentors, such as the impact that such training has on their mentoring skills once they are professionals, could also be tested. Last, given that emerging research has suggested that students in HSP are aware of and negatively affected by problems with professional competence in educators (Furr & Brown-Rice, 2016), future research should examine whether student-led mentorship is perceived to "bridge the gap" in areas where faculty mentors may lack competence.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, these findings suggest that graduate training does not consistently prepare psychologists for working with clients from diverse backgrounds. One reason for this could be due to lack of cultural competence and sensitivity on the part of faculty and supervisors (Furr & Brown-Rice, 2016). One way of supplementing this education on diversity issues in graduate training is through using graduate mentors, who may possibly have more competence in this area than do professionals.…”
Section: Promoting Competence In Individual and Cultural Diversitymentioning
confidence: 99%
“…Too often, responsibility for integrating the science and practice of psychology seems to be displaced onto the graduate students (Stone, ). In addition, 79.3% of clinical students and 75.4% of counselling students believed their programme was hypocritical, because students were expected to adhere to higher standards of professional demeanour than seen in their faculty members (Furr & Brown‐Rice, ).…”
Section: Introductionmentioning
confidence: 99%
“…Psychotherapy requires generic clinical skills such as insight, sensitivity, empathy and patience that are not always needed when supervising bright, young and motivated graduate students (Overholser, ). A survey of 1,284 American graduate students in psychology found that 28.2% of clinical psychology trainees and 31.7% of counselling psychology trainees had been negatively impacted by faculty members who displayed inadequate clinical skills (Furr & Brown‐Rice, ). Even more alarming, 56.3% of clinical students and 59.6% of counselling students expressed concern about faculty members with professional competency problems who were allowed to teach in their program (Furr & Brown‐Rice, ).…”
Section: Introductionmentioning
confidence: 99%